THE IMPLEMENTATION OF 2013 CURRICULUM 2016 REVISION ON ANECDOTE TEXT WRITING (CASE STUDY IN GRADE X SMK NEGERI 1 GONDANG KABUPATEN SRAGEN) - Rasyid Manshur; Sarwiji Suwandi; Suyitno Suyitno (Center of Language and Cultural Studies [CLCS], 2022)
This study is aimed to describe and explain: (1) the process of writing anecdote text based on 2013 curriculum 2016 revision which was conducted by the teachers of Indonesia Language subjects in class X SMK Negeri 1 Gondang Sragen, (2) the existing obstacles in the process of writing anecdote text 2013 curriculum 2016 revision in class X SMK Negeri 1 Gondang Sragen, and 3) the teachers’ efforts to overcome the obstacles encountered in the process of writing anecdote text based on 2013 curriculum 2016 revision in class X SMK Negeri 1 Gondang Sragen. This qualitative research uses case study approach. The data sources in this research were events (the process of writing anecdote text), informants (teachers and students), and documents (syllabus and lesson plan). The results show that the implementation of learning to write anecdote text based on 2013 curriculum 2016 revision needs more in-depth assessment in order to improve planning, implementation, and assessment. It is also based on the encountered obstacles occurred in the learning process. Thus, the implementation of the 2013 Curriculum 2016 revision which is in line with the concepts and regulations of the government can be achieved. This is also implied for the achievement of national education objectives. Keywords: 2013 curriculum, revision 2016, writing learning, anecdote text, SMK student